Transcriptional Regulation by Nuclear Corepressors and PGC-1α: Implications for Mitochondrial Quality Control and Insulin Sensitivity - Zhengtang Qi; Shuzhe Ding (PPAR Research)
The peroxisome proliferator-activated receptors (PPARs) and estrogen-related receptor (ERRα) are ligand-activated nuclear receptors that coordinately regulate gene expression. Recent evidence suggests that nuclear corepressors, NCoR, RIP140, and SMRT, repress nuclear receptors-mediated transcriptional activity on specific promoters, and thus regulate insulin sensitivity, adipogenesis, mitochondrial number, and activity in vivo. Moreover, the coactivator PGC-1α that increases mitochondrial biogenesis during exercise and calorie restriction directly regulates autophagy in skeletal muscle and mitophagy in the pathogenesis of Parkinson's disease. In this paper, we discuss the PGC-1α’s novel role in mitochondrial quality control and the role of nuclear corepressors in regulating insulin sensitivity and interacting with PGC-1α.